Accuracy of Turbulent Closure Models in Calculation of Thrust of a Low Reynolds Number Airfoil Used as a Propeller - Adek Tasri (Department of Mechanical Engineering, Universitas Andalas, 2022)
Unlike in the case of high Reynolds number airfoil, selecting a turbulent closure model for the low Reynolds number airfoil is still a challenge. A turbulent model used for high Reynolds number airfoil is not necessarily suitable for low Reynolds number airfoil due to the presence of separation bubbles in the low Reynolds number airfoil. In this study, we used two simple turbulent models, Spalart-Allmaras and k- , in calculating thrust coefficient of low Reynolds number airfoil used as propeller to determine their accuracy. It was found that there was a significant discrepancy between the numerical calculation results by both the turbulent model and the experimental data. The k- was a little more accurate than Spalart-Allmaras turbulent closure model.